Influence of Vacuum Precooling Pressure on SOD Enzyme Activity of Fresh Lycium barbarum and Molecular Dynamics Simulation - Hongbo ZHANG; Ningbo KANG; Lianghuan ZHOU; Jun ZHANG; Qianjin QU (Shipin gongye ke-ji)
In order to investigate the effect of vacuum precooling on superoxide dismutase (SOD) enzyme activity of fresh Lycium barbarum and its molecular level mechanism, this paper explored the activity of SOD enzyme in crude enzyme liquid extracted from fresh Lycium barbarum of Ningxia was determined under 900 Pa and 1100 Pa vacuum precooling final pressure. The structural changes of SOD enzyme under different vacuum precooling pressure treatments were studied using molecular dynamics simulation for 150 ns, which included the changes of root mean square deviation (RMSD), radius of gyration (Rg), total energy, potential energy, kinetic energy, bond angle energy, root mean square fluctuation (RMSF), number of hydrogen bonds, surface structure and solvent accessible surface area (SASA). Then the optimum pressure conditions for vacuum precooling treatment were selected. The results of experiments showed that the activity of SOD enzyme was the highest under 900 Pa. The results of molecular dynamics simulation showed that the total energy, potential energy, kinetic energy and bond angle energy of SOD enzyme were in a balanced and stable state. An increase in pressure could cause changes in the surface structure of proteins, reduced the number of hydrogen bonds, and continuously decreased the solvent accessible surface area. Under the condition of 900 Pa, the protein structure was the most compact, and binding pocket became wider and easier to bind to the protein. The activity of SOD enzyme protein decreased under 1100 Pa, the protein structure was damaged, and binding pocket became smaller. This study could provide a scientific reference for the study of fresh Lycium barbarum preservation and processing.